2005
DOI: 10.1158/1078-0432.ccr-04-2496
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Cytotoxicity of Proteasome Inhibitors and Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand in Chemoresistant Bcl-2-Overexpressing Cells

Abstract: Purpose: Bcl-2 overexpression is frequently detected in lymphoid malignancies, being associated with poor prognosis and reduced response to therapy. Here, we evaluated whether Bcl-2 overexpression affects the cytotoxic activity of proteasome inhibitors taken alone or in association with conventional anticancer drugs or tumor necrosis factor–related apoptosis-inducing ligand (TRAIL). Experimental Design: Jurkat cells engineered to overexpress Bcl-2 were treated with proteasome inhibitors (MG132, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 65 publications
5
30
0
Order By: Relevance
“…There exists a synergism in the apoptotic process presumably by downregulation of prosurvival signaling molecule AKT in addition to modulation of other important anti/proapoptotic molecules. It has been shown that proteasome inhibitors cooperate with TRAIL in inducing apoptosis in cancers with over expression of bcl2 (Nencioni et al, 2005). Our results demonstrate that EGCG that has also been shown to act as a proteasome inhibitor (Lam et al, 2004;Landis-Piwowar et al, 2005) might actually synergize with TRAIL in inducing apoptosis in LNCaP cells.…”
Section: Discussionsupporting
confidence: 51%
“…There exists a synergism in the apoptotic process presumably by downregulation of prosurvival signaling molecule AKT in addition to modulation of other important anti/proapoptotic molecules. It has been shown that proteasome inhibitors cooperate with TRAIL in inducing apoptosis in cancers with over expression of bcl2 (Nencioni et al, 2005). Our results demonstrate that EGCG that has also been shown to act as a proteasome inhibitor (Lam et al, 2004;Landis-Piwowar et al, 2005) might actually synergize with TRAIL in inducing apoptosis in LNCaP cells.…”
Section: Discussionsupporting
confidence: 51%
“…Although some potential mediators of this sensitization effect have been indicated, for example p21 (Lashinger et al, 2005), c-FLIP (Sayers et al, 2003), Bik and Bim (Nikrad et al, 2005), whereas others have been excluded, for instance Bcl-2 (Nencioni et al, 2005), Bax (He et al, 2004) and Bcl-xL (Johnson et al, 2003), the specific contribution of NF-kB to this phenomenon remained unclear. In fact, there is only one other report pointing to a differential role of proteasome versus NF-kB inhibition in the regulation of TRAIL-induced apoptosis in glioblastoma cells, possibly by blocking degradation of active caspases (Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that salinomycin is capable of inducing apoptosis in both wild-type p53 cells and p53-lacking cells, indicating that the induction of apoptosis by salinomycin is independent of the p53 status of the cell (34). Next, p53-lacking lymphoblastic leukemia cells were transfected with a plasmid encoding the human anti-apoptotic protein Bcl-2, leading to stable overexpression of Bcl-2 and resistance of the cells to apoptosis induced by chemotherapeutic drugs (37). In these cells, salinomycin was able to markedly induce apoptosis even at the low concentrations used for the induction of apoptosis in non-resistant cells (34).…”
Section: Effects Of Salinomycin On Human Cancer Cellsmentioning
confidence: 99%